Effects of MTHFR C677T Gene Polymorphism on Migraine Together with Biochemical and Clinical Parameters in Turkish Population - Nisari, Mustafa; Baydemir, Recep (Progress in Nutrition, 2020)
To detect the relation between methylenetetrahydrofolate reductase (MTHFR) gene C677T polymorphismand both of clinical and biochemical parameters. One hundred sixty migraine patients and onehundred twenty control group were included in the current study. Pain intensity of individuals were measured,biochemical, clinical parameters and MTHFR C677T single nucleotide polymorphism were detected. Statisticallyhigher occurrence MTHFR C677T genotype was detected in migraine group than control group.A statistically significant association between family history of migraine and MTHFR C677T genotypeswas detected. Also, statistically higher BMI, homocysteine and the total cholesterol levels were detected inMO and MA groups than control groups. When we take into consideration of the clinical parameters, onlystatistically significant difference was detected between MA and MO for attack frequency (attack/ monthly).The triglyceride and homocysteine levels were significantly higher in males than females but HDL levels andfolate were significantly higher in females than males. The frequency of CT genotype was significantly higherin cases with compression and allodynia than others in MA groups and cases with fatigue in both MA andMO subgroups. Also, cases without systemic complaints had significantly higher T allele frequency than caseswith systemic complaints in the MA subgroup. Because the labor losses of patients with migraine may causeimportant economic losses, performed studies for the fully understanding of the disease including genetic andenvironmental factors are important for the prevention of negativity caused by the disease.